Pengaruh Tingkat Pengetahuan Keselamatan Pelayaran terhadap Pemenuhan Fasilitas K3 (Kesehatan dan Keselamatan Kerja) di Atas Kapal - Suryani, Dedeh; Indriyani, Indriyani; Hendrawan, Andi; Pramono, Sri (Marine Science and Technology Journal, 2023)
Shipping safety is a must, it is an obligation for everyone to carry it out. And the fulfillment of safety facilities is a must that must be carried out or fulfilled by shipping companies. Shipping safety is inseparable from the people on board, namely the Ship's Crew (ABK), namely people who become the crew of the ship and the Nakoda as its leader. This study aims to prove the relationship between the level of knowledge and the fulfillment of shipping safety facilities. . The study used 5 ships and 61 samples and analyzed using kai squared . The results of the study show that there is a significant relationship between the level of knowledge and the fulfillment of shipping safety facilities.